Cocrystals of the green fluorescence protein chromophore analogue: coformer-induced switch between AIE and ACQ - Suresh, Sneha; Dabke, Niteen B.; Pandya, Rinu; Vanka, Kumar; Dutta, Madhusudan; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Fluorescent organic solids hold great potential for advancing photonics applications. However, tuning their solid-state photoluminescent emissions remains a significant challenge. In this study, we report the synthesis and characterization of five cocrystals (two cocrystal polymorphs) derived from a pristine imidazolinone derivative (A) and the various coformer molecules, namely 1,2,4,5-tetrafluoro-3,6-diiodobenzene, 1,2,4,5-tetrafluoro-3,6-dibromobenzene, perfluoronaphthalene, and 3,4,5-trifluorobenzoic acid. The structural and optical properties of these cocrystals were examined by using single-crystal X-ray diffraction, absorption spectroscopy, photoluminescence spectroscopy, and photoluminescence decay spectroscopy. Cocrystals I, II, and III are isomorphous pairs and exhibit three-dimensional isostructurality, where the coformer molecules bridge adjacent helices of compound A, leading to aggregation-induced emission. In contrast, the cocrystal polymorphs IVA and IVB developed using coformer 3,4,5-trifluorobenzoic acid form two-dimensional sheet-like structures mediated by pi-stacking interactions between the coformers and molecule A, with interplanar distances ranging from 3.2 to 3.5 & Aring;. These stronger pi-pi interactions promote nonradiative decay pathways, resulting in reduced or quenched fluorescence and an aggregation-caused quenching effect. To gain further insights into their electronic properties, theoretical analysis including frontier molecular orbitals, time-dependent density functional theory, Hirshfeld surface analysis, molecular electrostatic potential, and noncovalent interaction plots were performed.